Heat Supply of Field Hospital Operating under Emergency Conditions - A. P. Nesenchuk; T. V. Ryzhova; I. L. Kachar; A. V. Begliak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a possibility to use a heat generator in a heat supply system of a field hospital which is operating under emergency conditions. Comparison of heat efficiency with the data existing in the literature has been done in the paper.